Integration Processes as the Basic Mechanism of Forming the Opened Educational Space of an Educational Institution - Ivanna Pukas; Tatiana Franchuk (Pedagogical Discourse, 2018)
The article deals with the problems and perspectives of forming the open, personally directed educational environment on the basis of integration processes’ actualization, as well as the most important connections and dependencies in the context of modern education’s (general, professional, postgraduate) competent system. From the standpoint of educology the problem of the educational environment formation investigates as a dynamic self-developing system with a basic characteristic – openness. The essence of the educational environment as interaction of internal and external educational environments is analyzed. An example of a hierarchy of educational environments based on the logic of subordination of systems and subsystems is offered. They have common goal orientation and forms of constructive parity relationship, aimed at optimizing all segments of the integral educational system through forming favorable conditions for each subject’s self-realization the potential development. The basic principles of integration processes’ activation in the context of modern educational institution integral educational space are theoretically substantiated. The leading disintegration processes, which are caused by the traditional information-reproductive system, the basic principles of activation of integration processes in the context of a holistic open educational environment are presented. The emphasis is placed on the fact that the educational environment is programmed by the cooperation vectors of interdependent educational systems (for example, schools and higher educational institutions) both in the aspect of system modernization and the increase of theoretical and practical competence as to the innovative educational problems.